Ackermannviridae bacteriophage against carbapenem-resistant Klebsiella pneumoniae of capsular type 64 - Li, Juan; Feng, Yu; Luo, Huan; Fang, Qingqing; Yang, Yongqiang; Zong, Zhiyong (Frontiers in Microbiology, 2024)
Lytic bacteriophages (phages) are promising clinically viable therapeutic options against carbapenem-resistant Klebsiella pneumoniae (CRKP), which can be assigned to various types with sequence type 11 and capsular type 64 (ST11-KL64) predominant in China. The emerging resistance to phages is a major bottleneck hindering effective phage therapy, requiring more new phages to provide the flexibility for creating various phage cocktails. However, the majority of phages against ST11-KL64 CRKP belong to the genus Przondovirus of the family Autographiviridae, limiting the options for constituting cocktails. We recovered a novel lytic phage of the genus Taipeivirus within the family Ackermannviridae against ST11-KL64 CRKP from a river in China. We phenotypically characterized this phage and obtained its genome sequence for analysis. This phage can inhibit the growth of ST11-KL64 CRKP for 6.5 hours at a 0.1 multiplicity of infection and exhibits a narrow host range unable to attack CRKP strains of other 30 capsular types. This phage carries no genes encoding antimicrobial resistance, virulence, nor lysogeny, is stable to a wide range of temperatures and pH values, and therefore is suitable for phage therapy. Unlike other Taipeivirus phages, P01 has two tail spike proteins and a unique tail fiber protein. The distinct tail composition contributes to its activity against ST11-KL64 CRKP and the narrow host range. Taken together, we recovered a phage of a novel viral species with the potential for therapy, which expands the phage biobank against CRKP.